The story of my life - Keller, Helen (Signet Classics, 2010)
In this autobiography, initially published in 1903, Helen Keller recalls her remarkable life as a blind and deaf woman taught to communicate by Ann Sullivan. Here among other memories, Keller describes her epiphany at the water pump when she connected the physical world with its linguistic counterpart. Keller was eventually educated at Radcliffe University, where she graduated with honors.